Ocorrência e distribuição de espécies de Messatoporus Cushman (Hymenoptera, Ichneumonidae, Cryptinae) em áreas de Mata Atlântica de Angra dos Reis e Paraty, RJ - Lima, Thalita da Silva (2022)
The present work aimed to study the diversity, abundance and taxonomy of parasitoid wasps of the genus Messatoporus, on the islands of Angra dos Reis and Paraty, Rio de Janeiro, Brazil. The collections were carried out in ten areas, between continents and islands on the southern coast of the state of Rio de Janeiro. 37 Malaise traps were installed during the period from July 2016 to December 2018, at different altitudes with collections carried out every 15 days. A total of 19,780 Ichneumonidae (Hymenoptera) were collected, 3,348 belonging to the subfamily Cryptinae, 198 to the genus Messatoporus, where males represented 51% of the collected species and females 49%. Three new species were described: M. sp. nov.1, M. sp. nov. 2 and M. sp. nov. 3, in addition to 15 other morphospecies. The following species were identified: M. aurantius Santos, 2013, M. convexus Santos, 2013, M. ellipsicavus Santos, 2013, M. nigriscutus Santos, 2013, M. opacus Santos, 2013 and M. variegatus Szépligeti, 1916.M. aurantius, M. convexus, M. ellipsicavus, M. nigriscutus, M. opacus, and M. variegatus. The most abundant were morphospecies 10, with 79 individuals collected, and M. ellipsicavus, with 62 specimens collected. The results bring relevant knowledge for the occurrence and diversity of Messatoporus in atlantic forest, including some coastal islands.